The effect of cervical stabilization and thoracic spine extension exercises on neck functional ability for forward head posture patients - Fitri Yani; Faradilla Windy Putri A. Gani (Universitas Udayana dan Diaspora Taipei Medical University, 2024)
Background: The widespread usage of cell phones may encourage everyone to rely more on technology in all aspects of their lives. However, if technology use in daily tasks is not balanced with physical exercise, musculoskeletal problems may develop. The most common concern associated with this syndrome is forward head posture. This study aimed to determine whether giving cervical stabilization and thoracic spine extension exercises can increase neck functional ability for forward head posture patients. Methods: The study used an experimental design. There were 23 physiotherapy students of Universitas 'Aisyiyah Yogyakarta as samples for this study, who had forward head posture and underwent measurement of neck functional ability by using the neck disability index (NDI). The independent administrator randomly assigned the treatment and control groups. The interventions were s conducted three times a week for four weeks. Data analysis employed a paired sample T-test to assess the effect of treatment and control groups. An independent sample T-test was used to compare the impact of treatments and control groups. Results: The results of the paired sample T-test in treatment and control groups, with p-values=0.001, indicate that both interventions improved the functional ability of the neck. The difference between treatment and control groups tested by the independent sample T-test shows p-value=0.062 for the pre-test and (p-value=0.444), suggesting no difference in effectiveness between cervical stabilization and thoracic spine extension on neck functional ability for forward head posture conditions. Conclusion: There was no difference in the effect of cervical stabilization and thoracic spine extension on the functional ability of the neck for forward head posture.